Capacity for early detection, response and practice of villagers in relation to veterinary emergency preparedness for prevention, diagnosis and surveillance of Highly Pathogenic Avain Influenza (HPAI) in Suphanburi Province - Minet, Dubravka Selenic (Chulalongkorn University, 2006)
The purpose of this study was to evaluate the knowledge, practices, and reponses of Thai villagers in relation to avian influenza (AI), in Suphanburi province where ther was more than one outbreak with human fatal cases and to proviee this information to governmental and non governmental institutions for evaluation of all veterinary and health action taken during four waves of avian influenza outbreaks in Thailand. The study also describes socio-demographic characteristics, source of information on avian influenza and attitudes regarding satisfaction of affected farmers with governmental action and compensation. A cross-sectional analytical study with a self-admiinistered questionnaire and group discussion were used in this study with a systematic sampling method, using one adult per household. The results showed that respondents had a reasonably accurate knowledge about AI. About 68% of respondents had moderate knowledge about symptoms of sick birds and 58.3% had moderate knowledge regarding AI transmission; 67.2% have moderate knowledge about AI and 48.9% had moderate practice level. The survey result shows that the knowledge of respondents does not relate directly to their practices in relation to disease prevention, surveillance and diagnosis. The main source of avian influenza information was TV broadcasts. Correlation analysis showed that income was positively and highly significant correlated with basic knowledge score (r=0.227, p<0.002) and positively correlated with precaution (r=0.182, p<0.015). Significant association was found between knowledge of AI symptoms of affected poultry farmers (p<0.004). Positive significant association was highly significant association between knowledge and practice (p<0.001). Practice score was positive significant correlated with score for transmission knowledge (p<0.004). Taking into account that good practice is carried out by less than 50% of farmers means that the government needs to explain more about safety practices. The government has carried out a massive campaign to explain the dangers and to make people aware of AI but this has not had the expected impact on farmers who still do not fully believe the dangers.